Analisis Kepatuhan Wajib Orang Pribadi (OP) pada Kantor Pelayanan Pajak Pratama - Dian Priatiningsih; Fangela Myas Sari (Akuisisi : Jurnal Akuntansi, 2025)
This research uses quantitative methods. The population of this research is individual taxpayers registered at the Batang Regency Pratama Tax Service Office. The sample was determined using the accidental sampling method, namely collecting information from taxpayers who the researcher happened to meet. the sample was taken from the population of Taxpayers who have NPWP at KPP Pratama Batang Regency and a sample of 86 respondents were obtained. The data used in this research is a questionnaire using a likert scale of 1 to 5. The data analysis technique is multiple linear regression using SPSS version 20 software. The results of data analysis show that there is a partial influence on the independent variables. The conclusion from the results of this research is that tax understandingand tax justice having a positive and significant effect on individual taxpayer compliance